Homocysteine and Carcinoembryonic Antigen as Biomarkers for the Diagnosis of Malignant Pleural Effusion - Maira Fatima; Mohd Abdul Rehman; Iyyapu Krishna Mohan; NN. Sreedevi; Nazia Siddiqua; B.Yadagiri; KSS.Sai Baba; Mohammed Noorjahan (International Journal of Pharma and Bio Sciences, 2020)
Pleural effusion (PE) results from both malignant and benign conditions. Pleural fluid analysis mainly differentiate exudates from transudates. Malignant effusions are mostly exudates. Cytological examination is simple and noninvasive procedure which is commonly used to identify malignant effusions. In case of malignant exudates with negative cytology, tumor markers are often used in adjunct with routine biochemical parameters to differentiate malignant effusions from benign. Carcinoembryonic antigen (CEA) is the most commonly used tumor marker. The sensitivity of CEA for malignant effusions varies depending on the tumor origin. Homocysteine (HCY) was thought to be elevated in pleural fluid in malignant pleural effusions as the cancer cells have increased utilization of vitamin B12 and folate, leading to homocystinuria. Usually a combination of tumor markers increases the accuracy of diagnosis. The use of biomarkers on pleural fluid specimens may assist in the decision-making process, enhance clinical diagnostic pathways and speed up treatment. Hence the present study is taken up to determine the utility of CEA and HCY in the diagnosis of malignant pleural effusions. We enrolled 36 patients in the study. Based on pleural fluid cytology they were classified into two groups (i) Malignant Pleural Effusion (MPE) and (ii) Benign Pleural Effusion (BPE). Out of 36 patients, 18 were of MPE and 18 BPE. Median Pleural fluid HCY [median (range) in µmol/L] and CEA [median (range) in ng/ml] concentrations were higher in MPE 12.35 (8.8 -16.8) and 10.0 (6.0 - 11.9) than in those with BPE 7.5 (3.22 - 15.7) and 2.88 (0.625 - 7.44) respectively. For HCY, accuracy was 63.7%, at a cut off of 11µmol/L, sensitivity was 66.67% and specificity was 72.2%. For CEA, accuracy was 65.6%. At a cut-off 4.7 ng/ml of CEA, sensitivity was 61% and specificity was also 61%. Combination of HCY and CEA yielded an accuracy of 66.7%. Conclusion: Our study demonstrated pleural fluid CEA has higher accuracy than HCY for diagnosis of MPE. The combination of HCY and CEA in pleural fluid significantly improves the diagnostic accuracy of the test.